Wacana Kecantikan dan Body Image Perempuan di Jepang dalam Akun Instagram La Farfa Magazine - Meidhita Irsantri, Farissa; Purba, Esther Risma (Humanis, 2024)
Women's magazines in Japan play a major role in the formation of a discourse that emerges and is normalized in society. This research was conducted using descriptive qualitative method  and Visual Methodology Theory of  Gillian Rose is used to analyze how La Farfa Magazine in its Instagram social media has values, signs, and context meanings. A comparison with Non-no magazine, which is the dominant beauty and body image reference in Japan, was conducted to highlight La Farfa's differences with mainstream beauty media. The research found that La Farfa Magazine (@lafarfa_jp) has 6 aspects of difference that stand out, namely followers/followers, posts, comments, likes/likes, captions, and models used. The use of idols Naomi Watanabe, Kayo Noro, and news anchor at Nihon Television further expanded the discourse of plus-size beauty by no longer being limited to models to sell fashion for profit.